Impact of Authentic Leadership on Work Engagement and Organizational Citizenship Behavior: The Mediating Role of Motivation for Work - Leal Paredes, Marlon Santiago (Pontificia Universidad Católica del Perú, 2021)
The purpose of this research was to analyze the influence that the perception of authentic leadership produces on work engagement and organizational citizenship behavior through motivation for work. The study developed and evaluated a novel conceptual model oriented to understand the causal relationships between authentic leadership and work engagement and organizational citizenship behavior with the mediation of motivation for work. The population was chosen from the information given by the Directorio de Empresas y Establecimientos; it distinguishes 83,527 micros, small, and medium-sized enterprises (MSMEs) corresponding to all economic sectors, with multiple activities from the 24 provinces of Ecuador. These enterprises have a total of 1,783,852 employees. In this sense, a sample of 300 observations was considered, which were selected in a simple random way. The results revealed that authentic leadership produces a direct, positive, and significant impact on work engagement, motivation for work, and organizational citizenship behavior. Additionally, it was found that work engagement has a direct, positive, and significant effect on organizational citizenship behavior. Finally, results showed that motivation for work has a mediating role in the relationship between work engagement and organizational citizenship behavior. Thus, the study confirmed a new model representing a contribution to knowledge, which managers and entrepreneurs can use to devise new strategies for management in organizations.

El propósito de esta investigación fue analizar la influencia que produce la percepción del liderazgo auténtico sobre el compromiso laboral y el comportamiento de la ciudadanía organizacional a través de la motivación para el trabajo. Este estudio desarrolló y evaluó un novedoso modelo conceptual orientado a las relaciones causales entre el liderazgo auténtico, el compromiso laboral, el comportamiento de la ciudadanía organizacional y la motivación para el trabajo. La población fue elegida de la información obtenida por el Directorio de Empresas y Establecimientos que distingue 83,527 micro, pequeñas y medianas empresas (Mipymes) que corresponden a todos los sectores con múltiples actividades de las 24 provincias del Ecuador. Estas empresas tienen un total de 1,783,852 empleados. En este sentido, se consideró una muestra de 300 observaciones, las mismas que fueron seleccionadas de manera aleatoria simple. Los resultados revelaron que el liderazgo auténtico produce un impacto directo, positivo y significativo sobre el compromiso laboral, la motivación para el trabajo y el comportamiento de la ciudadanía organizacional. Adicionalmente, se identificó que el compromiso laboral tiene un efecto directo, positivo y significativo sobre el comportamiento de la ciudadanía organizacional. Finalmente, los resultados indicaron que la motivación para el trabajo tiene un papel mediador sobre la relación entre el compromiso laboral y el comportamiento de la ciudadanía organizacional. Por lo tanto, el estudio confirmó un nuevo modelo que representa una contribución al conocimiento que los gerentes y emprendedores pueden utilizar para idear nuevas estrategias para la gestión en las organizaciones.
Keywords: Liderazgo--Investigaciones; Comportamiento organizacional; Satisfacción en el trabajo; Motivación del empleado; https://purl.org/pe-repo/ocde/ford#5.02.04